Divulgação visual da ciência: um discurso entre imagem e palavra - Lombardi, Adalberto (2014)
The aim of the present work is to analyze the scientific communication in order to evaluate the extent to which that practice goes beyond the scientific articles of specialized journals or of traditional lectures which emphasize verbal speech. This will be done by the effective study of a sample of scientific communication material collected in journals found in newsagents. Printed production of scientific communication involves text, diagrams, drawings and maps without clear definitions of its object and intention to communicate. In order to meet this goal, the research brings about as analysis hypothesis: (1) scientific information must go through processes of transformation from the conceptual form, through translating operations to a less specialized and more suggestive and diagrammed language, attempting to induce in the mind of the average reader, the relationships involved, in each case, (2) the interaction with readers by means of diagrams, drawings, photographs, maps and colors expands their participation in the field of scientific culture, occasionally incorporating, to the perception of science communication, the experience of the reception previously acquired in the contact with audiovisual media, (3) the confrontation between image and words suggests that the study of diagrammatic relationships can help inferential expansion and the development of other cognitive perspective(s). The corpus of the research is the graphic communications in printed media, with emphasis on the development of forms of graphic design by digital media where the verbal language, in fragments, participate in the hybrid discursive formations, a suitable environment for semiosis where discreet and continuous signs combine having as a target the diagrammatic settings of a dialogic process. We are trying to verify how nonverbal languages compose with natural language in order to manage to configure the science semiotic processes. The scientific material selected should, methodologically, go through analytical procedures with regard to diagrammatic structure of the conceptual information, seeking to find out the inferential expansion in the hybrid formations of language. The theoretical foundations of the present research are distributed among the figures of the diagram and the inferences in C. S. Peirce, the notions of semiosfere and semiosis in Iuri Lotman and also the translating operation in Haroldo de Campos and Júlio Plaza